The Clinical Relevance of Information Index (CRII): assessing the relevance of health information to the clinical practice. (2nd April 2013) - Galvao, Maria Cristiane Barbosa; Ricarte, Ivan Luiz Marques; Grad, Roland M.; Pluye, Pierre
Abstract: Background: The high volume of health information creates a need for processes and tools to select, evaluate and disseminate relevant information to health professionals in clinical practice. Objectives: To introduce an index of the clinical relevance of information and to show that it is different from existing measures. Methods: A conceptual model of knowledge translation was developed to explain the need for a new index, whose application was verified by an exploratory study with two (quantitative and qualitative) phases. The Clinical Relevance of Information Index (CRII) was defined employing descriptive statistical analyses of assessments performed by health professionals. The model and the CRII were applied in a primary healthcare context. Results: The CRII was applied to 4574 relevance assessments of 194 evidence synopses. The assessments were performed by 41 family physicians in 2008. The CRII value of each synopsis was compared with the number of citations received by its corresponding research paper and with the level of evidence of the study, presenting weak correlation with both. Conclusion: The CRII captures aspects of information not considered by other indices. It can be a parameter for information providers, institutions, editors, as well as health and information professionals targeting knowledge translation.